Effect of phosphorus rate on growth, nodulation and biomass yield of green manure crops - Pramanik, MYA; Sarkar, MAR; Uddin, MS; Faruk, GM (Journal of the Bangladesh Agricultural University, 2010)
The effect of phosphorus rate on plant height, biomass yield and nodulation of green manure crops was investigated. Seven green manure species viz. Sesbania rostrata, Sesbania aculeata, Crotalaria juncea, Vigna unguiculata, Phaseolus mungo, Vigna radiata and Glycine max and three phosphorus rates viz. 18, 27 and 36 kg P ha-1 were used. Plant height was different for each green manure crops during the growth period though phosphorus fertilization had no significant effect on plant height and biomass yield. On the other hand, phosphorus fertilization had significant effect on nodulation of green manure crops. The number of nodules plant-1 increased significantly with the age of the plants up to 60 days after sowing (DAS) and thereafter declined sharply at 75 DAS. The highest number of nodules plant-1 was produced at 36 kg P ha-1 followed by 27 kg P ha-1. The lowest number of nodules plant-1 was produced at 18 kg P ha-1. Keywords: Green manure crops; Phosphorus; Growth; Nodulation; Biomass yield DOI: 10.3329/jbau.v7i1.4793 J. Bangladesh Agril. Univ. 7(1): 23-28, 2009